2017
DOI: 10.1177/0009922817691818
|View full text |Cite
|
Sign up to set email alerts
|

Constipation-Related Health Care Utilization in Children Before and After Hospitalization for Constipation

Abstract: We studied constipation-related health care among children before and after constipation admission. Index admissions for constipation in 2010-2011 were identified in the Truven Marketscan Database, which includes children receiving Medicaid in 10 states. We measured number of and spending for outpatient constipation visits 12 months before and after index hospitalizations. We also measured spending for constipation hospitalizations and rehospitalization rate. There were 780 index constipation admissions. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
(19 reference statements)
1
7
0
Order By: Relevance
“…However, as effective as inpatient cleanouts may be acute, 10% of children are readmitted for constipation within 12 months. 10 This is similar to rates observed for asthma, 11 an ambulatory care-sensitive condition in which high-quality outpatient care is believed to reduce hospitalizations. 12 Unnecessary testing and treatment are other sources of waste.…”
Section: Why Inpatient Cleanouts Are Unnecessarysupporting
confidence: 64%
See 1 more Smart Citation
“…However, as effective as inpatient cleanouts may be acute, 10% of children are readmitted for constipation within 12 months. 10 This is similar to rates observed for asthma, 11 an ambulatory care-sensitive condition in which high-quality outpatient care is believed to reduce hospitalizations. 12 Unnecessary testing and treatment are other sources of waste.…”
Section: Why Inpatient Cleanouts Are Unnecessarysupporting
confidence: 64%
“…Hospitalization may represent a reasonable investment if it effectively addressed the underlying condition and reduced future utilization. However, as effective as inpatient cleanouts may be acute, 10% of children are readmitted for constipation within 12 months 10 . This is similar to rates observed for asthma, 11 an ambulatory care‐sensitive condition in which high‐quality outpatient care is believed to reduce hospitalizations 12 …”
Section: Why Inpatient Cleanouts Are Unnecessarymentioning
confidence: 70%
“…Although obesity, with its effects, is perceived as a public health problem, constipation is sometimes trivialized. Affected patients have a high level of psychological distress (4), leading to a reduced quality of life (5,6), which both is resulting in increasing health-related costs (7).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Stephens et al showed in a publicly insured population the median spending for 1 constipation admission was 50 times the median spending for 12 months of outpatient constipation visits. 19 A visit in the 30 days before the ED visit represents a potential opportunity to manage this problem before abdominal pain or stool impaction occurs.…”
Section: Discussionmentioning
confidence: 99%